SELECTED PHYSICAL AND MECHANICAL PROPERTIES OF COMBINED WOOD BASED PANELS FROM WOOD FIBERS AND SAWDUST - Savov, Viktor; Mihajlova, Julia; Grigorov, Rosen (Innovation in Woodworking Industry and Engineering design, 2019)
The production of wood fiber mass is a very energy-intensive process This is also one of the reasons for the higher cost of this material in comparison of that at particleboards. One possibility to partially solving this problem is the inclusion of industrial wastes, which has not undergone a refining process, in MDF composition. There is a significant amount of industrial wastes resulting from logging – these are mainly the sawdust resulting from the processing of solid wood with a band saw. It should be pointed out that this method of obtaining solid wood materials is widespread, both globally and in Bulgaria. This report presents a study on the influence of the content of coniferous sawdust on the properties of combined panels from wood fiber and sawdust. Produced panels were with variation of sawdust content from 0 to 50% and respectively the fiber content was from 100 to 50%. The increase in sawdust content was with a step of 10%. The main physical and mechanical properties of panels were determined and experimentally-statistical equations for the influence of coniferous sawdust content on the properties of the panels were derived. It was determined at what percentage of sawdust the panels have properties that meet the requirements of the relevant standards for MDF.